2019
DOI: 10.1093/ndt/gfz091
|View full text |Cite
|
Sign up to set email alerts
|

The use of plasma donor-derived, cell-free DNA to monitor acute rejection after kidney transplantation

Abstract: Background After transplantation, cell-free deoxyribonucleic acid (DNA) derived from the donor organ (ddcfDNA) can be detected in the recipient’s circulation. We aimed to investigate the role of plasma ddcfDNA as biomarker for acute kidney rejection. Methods From 107 kidney transplant recipients, plasma samples were collected longitudinally after transplantation (Day 1 to 3 months) within a multicentre set-up. Cell-free DNA f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
86
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 25 publications
1
86
2
Order By: Relevance
“…At a threshold 52 cp/mL, it had a sensitivity of 73%, a specificity of 73%, a PPV of 13%, and an NPV of 98%. They believed that cfDNA fraction was subject to influences by recipient cfDNA levels which tended to increase during (27) presented the contradictory results and they found that plasma ddcfDNA did not outperform the diagnostic capacity of the serum creatinine in the diagnosis of acute rejection. Our study and three other studies all showed that cfDNA fraction has a high NPV for ABMR diagnosis, which means most of patients with negative cfDNA fraction (below the threshold) do not have ABMR, suggesting that donor-derived cfDNA fraction measurement may avoid unnecessary kidney transplant needle biopsy when the other types of allograft injury can be excluded, especially in patients on anticoagulation medication or patients for whom it is inconvenient to perform kidney needle biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…At a threshold 52 cp/mL, it had a sensitivity of 73%, a specificity of 73%, a PPV of 13%, and an NPV of 98%. They believed that cfDNA fraction was subject to influences by recipient cfDNA levels which tended to increase during (27) presented the contradictory results and they found that plasma ddcfDNA did not outperform the diagnostic capacity of the serum creatinine in the diagnosis of acute rejection. Our study and three other studies all showed that cfDNA fraction has a high NPV for ABMR diagnosis, which means most of patients with negative cfDNA fraction (below the threshold) do not have ABMR, suggesting that donor-derived cfDNA fraction measurement may avoid unnecessary kidney transplant needle biopsy when the other types of allograft injury can be excluded, especially in patients on anticoagulation medication or patients for whom it is inconvenient to perform kidney needle biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that measuring plasma dd-cfDNA is useful for the detection of allograft rejection/injury episodes in organ transplant recipients (3,20). However, elevated dd-cfDNA isn't specific for rejection; elevated levels are also observed in BKPyVAN in sporadic reports (4,9,10). This large-scale clinical study systematically assessed the performance of urine dd-cfDNA and dd-cfDNA% for discriminating BKPyVAN in adult kidney transplant recipients with BKPyV viruria.…”
Section: Discussionmentioning
confidence: 99%
“…Whitlam et al reports the plasma dd-cfDNA% was 1.5% in one patient with BKPyVAN (9). However, another study finds that plasma dd-cfDNA% remained below the threshold value (0.88%) in three cases of BKPyVAN (10). The majority of research on the use of dd-cfDNA for diagnosing acute rejection/injury has been focused on the proportion of dd-cfDNA in plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Kidney transplant recipients have an elevated AKI risk, which may result in graft loss [36,37]. Urinary tract infections are the most prevalent infectious complication in RTX patients and play a major cause in the development of AKI [1].…”
Section: Discussionmentioning
confidence: 99%